2017
DOI: 10.2147/jpr.s132682
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases and components of the endocannabinoid system in the knee joint are associated with biphasic pain progression in a rat model of osteoarthritis

Abstract: Matrix metalloproteinases (MMPs) are considered important in articular cartilage breakdown during osteoarthritis (OA). Similarly, the endocannabinoid system (ECS) is implicated in joint function and modulation of nociceptive processing. Functional interplay between ECS and MMPs has been recently indicated. Here, we tested if changes in the expression of selected MMPs and major ECS elements temporally correlate with the intensity of OA-related pain. Knee OA was induced in male Wistar rats by intra-articular sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…MMP-9 protein expressions were higher in the synovial joint fluid of patients with OA [82], and it has been demonstrated to be highly expressed in the early stages of wound healing due to its involvement in angiogenesis [83]. Pajak et al (2017) [84] added that MMPs' genes transcription was increased in the osteoarthritic rat model, with the highest expression in mRNA for MMP-9, which was firstly increased at day 2 then significantly decreased at day 28 compared to the gradual increase of MMP-13 to day 28. These data in concomitant with our results reveal that gelatinases initiate the degradative sequences in early OA, followed by collagenases, which play a pronounced role in OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 protein expressions were higher in the synovial joint fluid of patients with OA [82], and it has been demonstrated to be highly expressed in the early stages of wound healing due to its involvement in angiogenesis [83]. Pajak et al (2017) [84] added that MMPs' genes transcription was increased in the osteoarthritic rat model, with the highest expression in mRNA for MMP-9, which was firstly increased at day 2 then significantly decreased at day 28 compared to the gradual increase of MMP-13 to day 28. These data in concomitant with our results reveal that gelatinases initiate the degradative sequences in early OA, followed by collagenases, which play a pronounced role in OA progression.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Pajak et al further proved that the MIA model showed a biphasic progressive pattern of pain-like behaviors over 4 weeks. 8 In their study, an initial enormously increased weight-bearing deficit on day 2 after the MIA injection was followed by an alleviation of symptoms on days 6–12. On days 14–28, a second phase of chronic, progressive pain was observed.…”
Section: Introductionmentioning
confidence: 94%
“…Bearing in mind the 3R rule for the ethical use of animals in testing, we decided not to repeat the behavioral experiments performed previously by our group. In the previous studies, a behavioral pattern of changes occurring during OA progression was precisely described [ 24 , 54 ]. Both papers characterized OA-related pain behavior by Pressure Application Measurement test (Ugo Basile, Italy) and Dynamic Weight Bearing test (Bioseb, France).…”
Section: Methodsmentioning
confidence: 99%